2021
DOI: 10.3390/ijms22147502
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Δ9-Tetrahydrocannabinol Leads to Postnatal Catch-Up Growth and Dysmetabolism in the Adult Rat Liver

Abstract: The rates of gestational cannabis use have increased despite limited evidence for its safety in fetal life. Recent animal studies demonstrate that prenatal exposure to Δ9-tetrahydrocannabinol (Δ9-THC, the psychoactive component of cannabis) promotes intrauterine growth restriction (IUGR), culminating in postnatal metabolic deficits. Given IUGR is associated with impaired hepatic function, we hypothesized that Δ9-THC offspring would exhibit hepatic dyslipidemia. Pregnant Wistar rat dams received daily injection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…Oke et al further elucidated that higher hepatic expression of p66shc in ∆9-THCexposed offspring might also be regulated via epigenetic mechanisms. ∆9-THC offspring exhibited decreased expression of the hepatic microRNAs, miR-203a-3p and miR-29a/b/c [104]. Collectively, these microRNAs can influence the expression of p66Shc and long-term liver health [111][112][113][114].…”
Section: Cannabinoid-induced Fgr and Postnatal Hepatic Function And Lipid Metabolismmentioning
confidence: 95%
See 4 more Smart Citations
“…Oke et al further elucidated that higher hepatic expression of p66shc in ∆9-THCexposed offspring might also be regulated via epigenetic mechanisms. ∆9-THC offspring exhibited decreased expression of the hepatic microRNAs, miR-203a-3p and miR-29a/b/c [104]. Collectively, these microRNAs can influence the expression of p66Shc and long-term liver health [111][112][113][114].…”
Section: Cannabinoid-induced Fgr and Postnatal Hepatic Function And Lipid Metabolismmentioning
confidence: 95%
“…in rats leads to liver growth deficits at birth followed by complete catchup growth by 3 weeks whereby exposed offspring caught-up in body and liver weight relative to control [81]. In a follow-up study, Oke et al demonstrated for the first time that ∆9-THC-induced FGR led to male-specific augmentation of hepatic lipid synthesis (e.g., DGAT2, ACCa, FABP1, and SCD) as early as 3 weeks [104]. This was partially sustained (DGAT2) in adulthood, culminating to increased hepatic triglycerides and visceral adiposity [104].…”
Section: Cannabinoid-induced Fgr and Postnatal Hepatic Function And Lipid Metabolismmentioning
confidence: 99%
See 3 more Smart Citations